Four recommendations to tackle the complex reality of transdisciplinary, natural experiment research - Pearson, Amber L.; Pfeiffer, Karin A.; Buxton, Rachel T.; Horton, Teresa H.; Gardiner, Joseph; Asana, Ventra (Frontiers in Public Health, 2023)
Natural experiments are often used to study interventions in which randomization to control versus intervention conditions are impossible. Nature-based interventions (i.e., programs designed to increase human interaction with nature and improve human health) are commonly studied as natural experiments. We used a natural experiment design to explore the benefits of ecological rehabilitation of parks on biodiversity and resident health in low-income, minoritized neighborhoods in Detroit, MI. Given the complexities and interconnectedness of lived experiences, community needs, and ecological health, this research design has presented challenges. Based on our experiences, we pose four key recommendations for researchers and practitioners conducting natural experiments, nature-based interventions, and those working in low-income, minoritized neighborhoods. We use the explicit examples of challenges faced as rationale for these recommendations. The key recommendations are 1) Engage with community leaders, 2) Build a transdisciplinary team and work closely; 3) Examine privilege; and 4) Create a unified vision.